Genetic Variability and Association Analysis in Intervarietal Segregating Population of Clusterbean [Cyamopsis tetragonoloba (L.) Taub.] for Quantitative Traits - Singh, Bhagwat; Dahiya, G. S.; Yadav, N. R.; Sivia, S. S. (International Journal of Bio-resource and Stress Management, 2016)
Forty line of intervarital segregating population of clusterbean [Cyamopsis tetragonoloba (L.) Taub.] along with their parents were analyzed for genetic variability, correlation and path coefficients. Significant differences observed for various traits indicated substantial amount of variability existed among the genotypes for various traits, which indicated further genetic studies. High heritability coupled with high genetic advance was observed for number of branches plant-1, plant height, no. of clusters plant-1, days to flowering and seeds pod-1 indicating that selection would be rewarding for these characters. In general genotypic correlation coefficients were higher in magnitude than their phenotypic correlation coefficient, this indicated the association at genotypic level and control of sampling error. Seed yield plant-1 was found to be positively and significantly correlated with number of pods plant-1, number of cluster plant-1 and number of pods cluster-1. Path analysis revealed that characters such as number of pods cluster-1, number of clusters plant-1 and pod length were the major component traits of seed yield and hence these characters should be given priority in selection based on their high heritability coupled with high genetic advance also.